UPAYA ADAPTASI MASYARAKAT MUSLIM DENGAN BUDAYA TRADISIONAL DIKAWASAN SUKU TENGGER - Dwi Indah Lestari; Heri Kurnia (Universitas PGRI Adi Buana Surabaya, 2022)
The Tengger Tribe community who lives in the Argosari area in the Tengger Semeru National Park area with all its uniqueness that is able to attract public attention from domestic and foreign tourists. It can not be separated by the local culture of indigenous peoples who persist with all the uniqueness of culture as a characteristic of their personality. The various traditional activities or traditional cultures that develop in the area create unrest for the Muslim minority living in the argosari area. These cultures bring belief in the spirits of the ancestors with the form of offerings, which means they believe in gods other than Allah. The series of customs carried out by the Tengger tribe mostly use elements of Hindu religious culture. So, Muslim minorities are required to be tolerant and broad-minded. The Muslim minority must be selective in taking the positive and negative sides from various existing points of view, and be able to select negative and positive things that can be applied in life.